2019
DOI: 10.1177/2631831818824437
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Treatment Outcome of Risky Sexual Behaviour in Young Males with ADHD and Comorbid Alcohol Use Disorder: A Prospective Study

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is associated with risky sexual behavior (RSB). Alcohol use and high perceived stress in young adulthood contributes to this association. Previous studies have not found methylphenidate to reduce RSB in ADHD, as the population had comorbidities such as mood disorders and antisocial personality disorder. We aimed to study (a) the association of RSB with ADHD and severity of alcohol use among adolescents and young adult males with ADHD who had comorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Online sexual victimization and receiving sexual content messages (passive sexting) were signi cantly higher in non-users of ADHD medication and users of short-acting methylphenidate. Studies have shown that methylphenidate treatment in patients diagnosed with ADHD is successful in treating risky behaviors and risky sexual behaviors (39,40). In the literature, it is mentioned that methylphenidate treatment reduces risky sexual behaviors, but there is no speci c study addressing online sexual victimization, which is a form of sexual exploitation that does not involve physical contact (41).…”
Section: Discussionmentioning
confidence: 99%
“…Online sexual victimization and receiving sexual content messages (passive sexting) were signi cantly higher in non-users of ADHD medication and users of short-acting methylphenidate. Studies have shown that methylphenidate treatment in patients diagnosed with ADHD is successful in treating risky behaviors and risky sexual behaviors (39,40). In the literature, it is mentioned that methylphenidate treatment reduces risky sexual behaviors, but there is no speci c study addressing online sexual victimization, which is a form of sexual exploitation that does not involve physical contact (41).…”
Section: Discussionmentioning
confidence: 99%
“…ADHD scores (particularly the hyperactivity/impulsivity subscale) were significantly correlated with RSB (Spearmen’s ρ = 0.34, p < .05), and RSB was significantly reduced at both 3 months ( p = .02) and 6 months ( p = .004) relative to baseline. Further, ADHD total scores significantly predicted the reduction in RSB (odds ratio = 1.26, p = .01), but not in alcohol-use severity or in perceived stress ( Kumar et al, 2019 ), suggesting the improvement was unique to RSBs.…”
Section: Impact Of Pharmacological Treatmentmentioning
confidence: 93%
“…Two recent studies have examined this issue among the broader pool of adolescents and young adults. A 2019 study examined RSB in young men ( N = 31, ages 15–25 years) with diagnosed ADHD and comorbid alcohol use disorder after 6-month, open-label treatment with methylphenidate ( Kumar et al, 2019 ). ADHD scores (particularly the hyperactivity/impulsivity subscale) were significantly correlated with RSB (Spearmen’s ρ = 0.34, p < .05), and RSB was significantly reduced at both 3 months ( p = .02) and 6 months ( p = .004) relative to baseline.…”
Section: Impact Of Pharmacological Treatmentmentioning
confidence: 99%